2018
DOI: 10.1093/jcag/gwy067
|View full text |Cite
|
Sign up to set email alerts
|

The Gluten Free Diet: Assessing Adherence in a Pediatric Celiac Disease Population

Abstract: Background A strict, lifelong, gluten-free diet (GFD) remains the sole treatment for celiac disease (CD). The assessment of adherence to the GFD in pediatric studies is often based on self-report and visual analogue scales which lack proven validity. We sought to compare parental-report of GFD adherence to expert registered dietitian (RD) assessments, the best available standard. Methods Parents of children with biopsy-proven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Reported adherence to a GFD was high: 92% and 100% in children with T1DCD and CD, respectively. For children with CD, other Canadian studies have found overall, self-reported adherence ranging from 69% to 95% ( 11 , 12 ). For patients with T1DCD, previous studies suggest that adherence, both self-reported and by dietician or serological assessment, varies greatly, from 25% to 69% ( 13–16 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reported adherence to a GFD was high: 92% and 100% in children with T1DCD and CD, respectively. For children with CD, other Canadian studies have found overall, self-reported adherence ranging from 69% to 95% ( 11 , 12 ). For patients with T1DCD, previous studies suggest that adherence, both self-reported and by dietician or serological assessment, varies greatly, from 25% to 69% ( 13–16 ).…”
Section: Discussionmentioning
confidence: 96%
“…For patients with T1DCD, previous studies suggest that adherence, both self-reported and by dietician or serological assessment, varies greatly, from 25% to 69% ( 13–16 ). Self-reported adherence has been shown to overestimate true adherence in comparison to evaluation by a registered dietitian ( 12 ). However, the high rates of adherence reported for both groups in this study are supported by participants with available recent TTG results, among whom 85% of T1DCD and 75% of CD had TTG levels within reference range.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to a GFD was evaluated at 3, 6 and 12 months using the questionnaire from Green, Expert Dietician Evaluation of Gluten-Free Diet Adherence for Children. According to the Green measures, adherence is scored across five categories: Excellent, Good, Fair, Poor and Not gluten free [ 22 ]. Excellent and good are considered indicative of a patient following a GFD.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary adherence was assessed with the use of two validated questionnaires: (i) a GFD compliance questionnaire [20] and (ii) the Celiac Disease Adherence Test (CDAT) [21]. For pediatric patients, the questionnaires were filled by the parents or guardians, whereas older children actively participated in the process, which is common practice in research studies involving dietary recalls [22][23][24]. The results were used to assess the patients' attitudes to a GFD and discuss problems that could undermine dietary adherence.…”
Section: Dietary Consultationsmentioning
confidence: 99%